Calculation of radial force of radial HTS magnetic bearing. (June 2021) - Guan, Xiang; Zou, Yincai; Shang, Jin; Zheng, Liangwei; Bian, Xing; Wu, Jihao; Li, Qing
Highlights: The three-dimensional complete model of radial HTS magnetic bearing is established. The calculation results are basically consistent with the experimental results. Further characteristic analyses about radial HTS magnetic bearing are carried out. Abstract: Radial force (radial stiffness) is an important performance index of radial HTS magnetic bearing. However, it is difficult to calculate it due to the complexity and particularity of the structure. It is of great significance to establish an effective and convenient method to predict the radial force of radial bearing. In this paper, the moving mesh of COMSOL Multiphysics® software is introduced into the three-dimensional complete modeling of radial HTS magnetic bearing for the first time, so that the relative motion between the permanent magnet rotor and the HTS stator can be described easily. The complex boundary coupling can be avoided, and then the levitation force under different rotor displacements can be solved quickly. Compared with the traditional methods, this method is simple and convenient. At the same time, the effectiveness of the calculation is verified by the experimental results. Based on this method, the radial HTS magnetic bearing system with different geometric dimensions, different physical parameters and different motion forms can be calculated. Therefore, the results of this paper provide convenience for the design and characteristic research of radial HTS magnetic bearing.